2013
DOI: 10.1155/2013/507872
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Transient and Sodium‐Calcium Exchange Current in Human versus Rabbit Sinoatrial Node Pacemaker Cells

Abstract: There is an ongoing debate on the mechanism underlying the pacemaker activity of sinoatrial node (SAN) cells, focusing on the relative importance of the “membrane clock” and the “Ca2+ clock” in the generation of the small net membrane current that depolarizes the cell towards the action potential threshold. Specifically, the debate centers around the question whether the membrane clock-driven hyperpolarization-activated current, I f, which is also known as the “funny current” or “pacemaker current,” or the Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…AP waveforms and Ca i transient are close to experimental traces reported by Verkerk et al [7,12]. In particular the model well describes AP morphology, both during the upstroke and during the diastolic depolarization phase.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…AP waveforms and Ca i transient are close to experimental traces reported by Verkerk et al [7,12]. In particular the model well describes AP morphology, both during the upstroke and during the diastolic depolarization phase.…”
Section: Discussionsupporting
confidence: 85%
“…In order to mimic the experimental [Ca 2+ ] i data recorded by Verkerk et al [12] (transient range and amplitude) the following changes have been applied: I NaCa. We reduced the maximal I NaCa activity by 60% to increase diastolic Ca 2+ level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations result from notable interspecies differences in the dynamics and contributions of the calcium handling proteins, in the density of each current, and their regulation. Very few studies, however, have reported data from single cells that were dissociated from an excised human SAN [42,110] . Each of the studies was performed with isolated cells from a single SAN, but it was possible to compare a few electrophysiological parameters with rabbit cells.…”
Section: Human Embryonic Stem Cell-derived Cardiomyocytes: a Model Fomentioning
confidence: 99%